Sensitivity to Thyroid Hormone Indices Are Closely Associated With NAFLD - Lai, Shuiqing; Li, Jiarong; Wang, Zixiao; Wang, Wei; Guan, Haixia (Frontiers in Endocrinology, 2021)
Background: Previous studies on the association between thyroid function with non‐alcoholic fatty liver disease (NAFLD) have been contradictory. Acquired resistance to thyroid hormone theory might provide a reasonable explanation for these contradictions. We aimed to analyze the association between sensitivity to thyroid hormone indices with NAFLD. Methods: A total of 4,610 individuals from the health medical center of the First Hospital of China Medical University were included in this study. The previously used thyroid feedback quantile-based index (TFQIFT4) was calculated. Also, we substituted free triiodothyronine (FT3) into the TFQI formulas to get TFQIFT3 index. NAFLD was defined using abdominal ultrasound. Results: Study results showed that FT3/FT4 and TFQIFT3 were positively correlated with the triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels (P<0.05) and negatively correlated with high-density lipoprotein cholesterol (HDL-C) level (P<0.05). In contrast, TFQIFT4 was positively correlated with HDL-C level (P < 0.05). After adjustment for multiple confounders, FT3, FT3/FT4, and TFQIFT3 were positively associated with the risks of hyper-TG (hyper-triglyceridemia), hyper-TC (hyper-cholesterolemia), hyper-LDL (hyper-low-density lipoprotein cholesterolemia) and NAFLD (P < 0.05). However no association was observed between TFQIFT4 with the risks of dyslipidemia and NAFLD. Conclusion: TFQIFT3 and FT3/FT4 can be used as new indicators for predicting dyslipidemia and NAFLD, while TFQIFT4 has insufficient evidence in predicting dyslipidemia and NAFLD.